Propuesta de un sistema de enfriamiento con agua para la cinta de caucho extruido de la referencia del zapato Discovery en la compañía Croydon Colombia S.A. (2019)
A proposal for a water cooling system was developed for the Discovery rubber tape, extruded in the company Croydon Colombia S.A. This proposal seeks to reduce by 75% the waste currently generated in the extrusion line, going from 108 million pesos in waste to approximately 27 million pesos, which is caused by the dimensional distortion of the rubber tape, and thus improve the production process.